Pengaruh Komposisi Susu, Tepung Telur dan Tepung Beras terhadap Kualitas dan Organoleptik Biskuit - E. Vebriyanti; R. Kurniawan (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
The research objectives are determination of concentration of milk, rice flour and egg powder on protein, fat, crude fibre, and organoleptic evaluation on biscuit. The experiment was designed by using Randomized Block Design with 4 treatments: A(egg powder 20%, skim milk 33%, rice flour 7%), B (egg powder 25%, skim milk 25%, rice flour 10%), C (egg powder 30%, skim milk 17%, rice flour 13%), D (egg powder 35%, skim milk 9%, rice flour 16%), and each treatment was repeated 5 times. Parameters observed were protein, fat, crude fibre, and organoleptic of biscuit. Result shown, the concentration of milk, rice flour and egg powder affected of protein, fat, crude fibre, and organoleptic of biscuit highly significant (P<0.01). In conclusion, the best concentration of milk, rice flour, and egg powder for biscuit were 9%, 16%, and 35 % respectively.